Lights and shadows in the diagnosis of cerebral death - D'Onofrio, Felice (Medicina e Morale, 1991)
In recent years the new organ transplantantion techniques, especially those applied to a beating heart, have raised many problems and particularly in assessing the reality of death. Brain death, with the following suspension of circulatory and respiratory functions, certainly appears to be the most reliable way to assess the end of life. There are stili conflicting opinions about the assessment of brain death at both cortical and spinal levels. Starting from these contradictory data reported in the literature, the author reviews the problem, focuslng in particular on the validity of EEG and other investigations related to the neurovegetative activity. The importance of transplantation is emphasized together with that of organ supply, but the importance of really assessing the end of all nervous activity at various cerebral levels is also stressed, with the final recommcndation that no subjcct can ever be considered a donor if there is some doubt about his brain activity.